Cytotoxic terpenoids from Nardophyllum bryoides - Sánchez, Marianela (2010)
The investigation of the ethanol extract of fresh aerial parts of the Patagonian shrub Nardophyllum bryoides collected in the province of Chubut, Argentina, yielded eleven terpenoids. These include: three seco-ent-halimane diterpenoids (1-3), two ent-halimanes (4-5) and six pentacyclic oleanane and ursane triterpenoids (6-11). Four of these compounds (2, 6, 8 and 11) are hitherto unknown, while two others (1 and 4) have been previously reported but only as synthetic products. Several of these compounds showed moderate cytotoxicity against a human pancreatic adenocarcinoma cell line while compounds 4 and 5 were active at micromolar concentrations. The main component, seco-chiliolidic acid (1), could be isolated from this extract in large amounts, turning N. bryoides into a sustainable source of this bioactive compound.